PENGARUH ATRAKTOR RUMPON TERHADAP HASIL TANGKAPAN ALAT TANGKAP BAGAN (LIFT NET) DI PERAIRAN DEMAK - Bogi B Jayanto; Asriyanto .; A. Rosyid; H. Boesono (LPPM Universitas Pekalongan, 2014)
One kind of fishing gear that use to captured phototaxis positif fish is Lift Net. Lamp was no longer used as fish aggregating device for lift net because it was uneffective and unefficient to gathered fish target. If the problem still continued it can raised fuels consumption for lamp attractor. Another fish aggregating device “rumpon” was a solution for lift net operation. Research objectives were to increase effectivity, efficiency and fishing production, and hopefully it can raise fisheries income. Keyword : Liftnet, Rumpon, Demak Seawaters